2010
DOI: 10.1096/fj.10-161471
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral deficits and progressive neuropathology in progranulin-deficient mice: a mouse model of frontotemporal dementia

Abstract: Progranulin haploinsufficiency causes frontotemporal dementia with tau-negative, ubiquitin-positive neuronal inclusion pathology. In this study, we showed that progranulin-deficient mice displayed increased depression- and disinhibition-like behavior, as well as deficits in social recognition from a relatively young age. These mice did not have any deficit in locomotion or exploration. Eighteen-month-old progranulin-deficient mice demonstrated impaired spatial learning and memory in the Morris water maze. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
141
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 28 publications
16
141
0
Order By: Relevance
“…This is consistent with the large number of activated CD68 positive microglia in GRN mouse models (Lui et al, 2016; Martens et al, 2012; Yin et al, 2009, 2010) and patients with GRN mutations, especially in frontal white matter (Lant et al, 2014; Taipa et al, 2017), which could cause white matter damage through excessive phagocytosis. We also identified many amoeboid CR3/43 positive microglia in areas of severe WMH, suggesting that microglia with antigen-presenting cell function were particularly active in these regions, which has not been described previously in FTD.…”
Section: Discussionsupporting
confidence: 78%
“…This is consistent with the large number of activated CD68 positive microglia in GRN mouse models (Lui et al, 2016; Martens et al, 2012; Yin et al, 2009, 2010) and patients with GRN mutations, especially in frontal white matter (Lant et al, 2014; Taipa et al, 2017), which could cause white matter damage through excessive phagocytosis. We also identified many amoeboid CR3/43 positive microglia in areas of severe WMH, suggesting that microglia with antigen-presenting cell function were particularly active in these regions, which has not been described previously in FTD.…”
Section: Discussionsupporting
confidence: 78%
“…in the brain (Ahmed et al, 2010;Yin et al, 2010), we observed progressive, substantial thinning of the RNFL and a loss of ganglion cell layer (GCL) cells in 18-mo-old Grn-KO mice (Fig. 1, H-J).…”
Section: Results and Discussion Early Retinal Abnormalities In Humansmentioning
confidence: 87%
“…Mutations in the GRN gene that cause progranulin haploinsufficiency are a common cause of familial FTLD-TDP (Baker et al, 2006). Aged Grn-KO mice exhibit FTD-like behavioral abnormalities but lack TDP-43 mislocalization or neurodegeneration in cortical regions (Ahmed et al, 2010;Yin et al, 2010;Martens et al, 2012).…”
mentioning
confidence: 99%
“…Disruption of both the ubiquitin-proteasome system and the autophagy-lysosomal system is one of the characteristic features of FTLD with TDP-43 inclusions in the cytoplasm of neurons [27], and impaired production of PGRN is involved in this pathology [5][6][7]. Previous studies reported increased TDP-43 phosphorylation in PGRN-deficient mice [11,13,28]. In the present study, TDP-43 colocalized with p62 in the cytoplasm of neurons as well as the phosphorylated TDP-43 aggregate in the VPM/VPL were only observed in aged PGRN-deficient mice.…”
Section: Discussionmentioning
confidence: 99%